2020
DOI: 10.24903/jam.v4i1.776
|View full text |Cite
|
Sign up to set email alerts
|

Edukasi Kesehatan Reproduksi Remaja

Abstract: Masa remaja adalah periode transisi dari anak-anak hingga dewasa. Periode ini sangat penting dalam menentukan masa depan bangsa. Kesehatan dalam reproduksi remaja meliputi fungsi, sistem, dan proses dalam reproduksi. Edukasi kesehatan reproduksi bagi remaja merupakan hal penting sebagai upaya menghindari kekerasan dan penyimpangan seksual berbasis gender bagi remaja . Kurangnya edukasi terhadap hal yang berkaitan  dengan reproduksi mampu  memicu terjadinya hal-hal yang tak diinginkan di antaranya seks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
0
3
0
18
Order By: Relevance
“…Some literature shown that positive behavior and perception of pregnancy or childbirth were found in higher educational status of mothers [66]. Likewise with the dissemination of reproductive health materials, this also affected the formation of positive perceptions among teenager girls regarding pregnancy and childbirth that they will face [1], [29], [67], [68].…”
Section: Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some literature shown that positive behavior and perception of pregnancy or childbirth were found in higher educational status of mothers [66]. Likewise with the dissemination of reproductive health materials, this also affected the formation of positive perceptions among teenager girls regarding pregnancy and childbirth that they will face [1], [29], [67], [68].…”
Section: Literature Overviewmentioning
confidence: 99%
“…So many efforts have been conducted to reduce maternal and infant mortality, but those have not provided optimal results. Various counselling and education of reproductive health were very intensively carried out in several areas [1]- [5]. Socialization of Maternal Health and distribution of Maternal Books in the community, in order to increase the mothers' knowledge of healthy pregnancy and labour, have been carried out to the basic layers of society [6]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…Kehamilan remaja merupakan masalah yang sering terjadi pada remaja saat ini. Kebanyakan dari mereka belum mendapatkan penyuluhan tentang kesehatan dan resiko kehamilan di usia muda (Fatkhiyah et al, 2020). Dampak dari kehamilan pada usia remaja adalah abortus, kehamilan yang beresiko untuk terjadinya pre-eklamsia, anemia, bayi prematur, Bayi Berat Lahir Rendah (BBLR), kematian bayi, kanker alat reproduksi, karena pada usia 12-17 tahun rentan terjadi perubahan sel dalam mulut rahim (Widyaningsih, 2021).…”
Section: Pendahuluanunclassified
“…Termasuk hak dan kebebasan untuk bereproduksi secara aman, efektif, tepat, terjangkau, dan tidak melawan hukum. [1][2][3] Kesehatan reproduksi di kalangan wanita merupakan masalah yang penting untuk diperhatikan. Beberapa penyakit infeksi organ reproduksi wanita adalah trikomoniasis, gonore, klamidiasis, dan sifilis.…”
Section: Pendahuluanunclassified